Risk and Legal Consequences of Beauslim Slimming Products - Sandjaya, Edithya Widy; Kurnia, Ida (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The background of this study is the widespread use of slimming products in Indonesia and reports of health risks from hazardous ingredients, highlighting gaps between legal norms and practical enforcement. The research problem focuses on business liability and the legal consequences of distributing Beauslim slimming products. This study employs normative juridical research with statute, case, and analytical approaches. Secondary data include primary legal materials such as Law No. 8 of 1999 on Consumer Protection, Law No. 36 of 2009 on Health, the Civil Code (KUHPerdata), and BPOM regulations, as well as secondary literature and media reports. Data were analyzed qualitatively to examine the alignment and gaps between normative obligations and business practices. The results indicate that while laws mandate accountability, transparency, and accurate labeling, enforcement remains weak. Many hazardous products continue circulating, showing a gap between law and practice. Stronger regulation, corporate compliance, and consumer awareness are essential to minimize risks and ensure accountability.